2011
DOI: 10.5005/jp-journals-10024-1036
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Dimensional Precision of Different Silicone Impression Materials

Abstract: Objectives:To investigate the accuracy of four commercial types of additional silicone impression materials (AFFINIS ® , Virtual ® , Relay 2002 CD ® and Silagum ® ). Materials and methods:The accuracy of impression material was measured indirectly by measuring three dimensions on stone cast poured from impressions of a stainless steel master model. The three dimensions on stone cast were measured at 1 hour, 2 days, 1 and 2 weeks after making the impression. Two impression techniques were used in the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Changes in the distances between the abutments can compromise the marginal adaptation of fixed prostheses [14]. Values similar to those obtained in the present study have been found with variations of up to 20  μ m for the distance between abutments [4, 7–9]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Changes in the distances between the abutments can compromise the marginal adaptation of fixed prostheses [14]. Values similar to those obtained in the present study have been found with variations of up to 20  μ m for the distance between abutments [4, 7–9]. …”
Section: Discussionsupporting
confidence: 86%
“…In this study, casts obtained from the first pour, at one hour, the results found showed smaller variations than those shown in other studies, in which the same impression technique was used [9]. In one such study, variations were 110  μ m for the diameter of the abutment, 50  μ m for the height of the abutment, and 50  μ m for the distance between abutments [10].…”
Section: Discussionmentioning
confidence: 57%
“…1 The material is divided into two pastes, base and catalyst. Crosslinking occurs when the vinyl groups react with the hydride groups, which are catalyzed by platinum without generating by-products.…”
Section: Introductionmentioning
confidence: 99%
“…With silicone, storage conditions and dimensional accuracy are not a problem 16 and the silicone moulds can be used for more than one TR. Castelnuovo and Tjan 7 found a cooling effect of putty silicone moulds when they had been previously cooled in a fridge for 30 minutes but not when the mould was at room temperature.…”
Section: Discussionmentioning
confidence: 99%